2002
DOI: 10.1103/physreve.65.046409
|View full text |Cite
|
Sign up to set email alerts
|

Plasma instability of a vacuum arc centrifuge

Abstract: Ever since conception of the vacuum arc centrifuge in 1980, periodic fluctuations in the ion saturation current and floating potential have been observed in Langmuir probe measurements in the rotation region of a vacuum arc centrifuge. In this work we develop a linearized theoretical model to describe a range of instabilities in the vacuum arc centrifuge plasma column, and then test the validity of the description through comparison with experiment. We conclude that the observed instability is a ''universal'' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In this paper, a two-fluid model, which was developed originally for the vacuum arc centrifuge by Hole et al 33,34 to explain oscillations observed in the density and electric potential, is applied to study low frequency oscillations observed in WOMBAT. We show that the equilibrium and perturbed density profiles and the space potential profile from the model and data are consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a two-fluid model, which was developed originally for the vacuum arc centrifuge by Hole et al 33,34 to explain oscillations observed in the density and electric potential, is applied to study low frequency oscillations observed in WOMBAT. We show that the equilibrium and perturbed density profiles and the space potential profile from the model and data are consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 also shows that the current in the longitudinal cup is not altered during the high voltage pulses. An oscillation of about 25 kHz persisting throughout the discharge is attributed to drift waves, 12 with no significant negative perturbation being seen beyond the amplitude of this oscillation. The numerical simulations done so far by Rej et al 8 and Kostov et al 9 assumed low density ͑n ϳ 10 9 cm −3 ͒ plasmas with sheath thicknesses of several centimeters, in which the confined electron layer is formed a few millimeters from the electrode's surface.…”
mentioning
confidence: 96%
“…5, with the highest values occurring at r 10 mm. This motivates comparison with the theoretical eigenmode potential V th r [15]. The finite spatial resolution of the measurements, primarily determined by the Langmuir probe radial extent of 2 mm, was accounted for by convolving V th r with a Gaussian kernel function K r of corresponding width.…”
Section: Prl 99 205004 (2007) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 99%
“…The most striking feature is a 28 kHz quasiperiodic oscillation, modulated by a slowly varying envelope, whose ÿ3 dB bandwidth is 10 kHz. By comparing field profiles with a linear analysis based on a steady state model in rigid body motion, the oscillation was identified as a density gradient driven drift wave [15], propagating axially and azimuthally. The azimuthal velocity was approximately the same as that of the plasma rotation.…”
mentioning
confidence: 99%
See 1 more Smart Citation